Modelo integrativo sobre o comportamento do usuário na Busca e uso da informação: aplicação na área de saúde. - Tabosa, Hamilton Rodrigues (2016)
The objective of this thesis is to build an integrative model of search behavior and use of information based on the models of Ellis (1989), Krikelas (1983), Kuhlthau (1991), Taylor (1986) and Wilson (1981, 1996 and 1999) and validate it through the application with the information of users not specialized in healthcare (patients, except for students and professionals). The theoretical foundation came from the study of these models, as well as specialized literature in relation to the identification of information needs, search processes and use of information, in addition to addressing the concepts of Information and Health Science, as well as behavioral studies from theoretical psychology area. Through a phenomenological study, we build an integration of models and consolidate the final proposal for a single integrative model of search behavior and use of information. For validation, interviews were conducted in-depth and technical application of the critical incident with General Hospital patients of the Dr. Carls César de Oliveira, in Fortaleza. The theoretical and practical research presented validates the integrative model of search behavior and use of the proposed information as a tool to identify regularities about the search behavior and use of information unskilled users in healthcare and is also capable of application in the study of other audiences, characterized as a general model of search behavior and use of information. This statement stems from the fact that all aspects, phases and stages of the information behavior of the subjects in this study fall (are represented) in the integrative model built, being able to bring these results: the subjects of this research feel the need for information as soon realize a disease in themselves or a family member; they throw themselves in the search for information immediately, even without knowing formal sources of information in the area, through the Web, performing Google searches through popular terms and description of symptoms; at the beginning of the search, they feel insecure for not knowing the most effective words to use in the search strategies, but rely on Google's capability to provide information they deem relevant; they don´t admit, but prefer informal sources of information, which spread testimonials from others who have experienced the same health problems, and are able to identify drugs; there are users who only seek medical attention when they can not find treatment and healing on their own Web; there are users who seek information to better understand and talk about her condition with the doctor; they have urgency in the search for information because they rush in curing the disease not only because of the physical nuisance they cause, but also for fear of losing their jobs due to the delivery of medical certificates and away from social contact with family and friends; the Web is used as a means of access to information that is used for self-diagnosis and self-medication. Research on the search behavior and use of information made from the application of integrative model will bring wider results and provide scientific inputs that can be used by managers of information units at the planning and implementation of products and services.